Unlocking the Potential of MBOs - Roberto Duran-Fernandez (ZBW - Leibniz Information Centre for Economics, 2023)
This paper analyzes Management Buyouts (MBOs), where management teams acquire their companies. It explores various MBO types, such as Traditional, Employee, Management Employee, Divisional, and Buy-in Management Buyouts, each with distinct characteristics. The rationale for MBOs includes investor exit strategies and the alignment of management incentives for better company performance. Key triggers for MBO development include financial sector liberalization and a specialized financial ecosystem. Success factors for MBOs are identified as cash generation capacity and effective management. The paper also discusses the life cycle of MBOs, their impact on productivity and human capital, and the complexities involved, such as information asymmetry and agency problems. This paper contributes to the understanding of MBOs, providing insights that can inform both academic research and practical applications in the dynamic world of corporate finance.
Keywords: G34; M12; 650; Management Buyout (MBO); Employee Buyouts (EBO); Management Employee Buyouts (MEBO); Divisional Buyout (DBO); Buy-in Management Buyout (BIMBO)